Autoethnography as a Way to Foster Critical Thinking Skills for Academicians in Adult and Higher Education: A Queer (Asian) Crit Perspective and Example - Mitsunori Misawa (Adult Education Research Conference, 2014)
This paper will focus on how autoethnography helps adult educator foster critical thinking skills in adult and higher education and will address the following areas: autoethnography, critical thinking, and examples of the autoethnographic teaching methodology. This paper will conclude with some discussion and implications for implementing autoethnography in teaching adults.